Pengaruh Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan PD Sahang Mas - Farrel Andreas; Parama Santati; Wita Farla (Politeknik Negeri Ambon, 2023)
To improve employee performance, every organization needs to pay attention to the job satisfaction of its employees. One of the factors that can affect employee job satisfaction is the environmental conditions in the place where he works, both physical and non-physical. This study aims to analyze the effect of the physical work environment on job satisfaction of PD Sahang Mas employees. The population in this study were all employees of PD Sahang Mas, totaling 33 employees. With saturated sampling technique, the number of samples used in this study amounted to 33 employees. The data collection method used was questionnaires using a 5-point Likert scale. The instrument test was carried out using validation and reliability tests. The analysis technique used is simple linear regression analysis using the SPSS application. Based on the results of the analysis it was concluded that the physical work environment has a positive and significant effect on the job satisfaction of PD Sahang Mas employees.